Decomposition of leaf and fine root residues of three different crop species in tropical peat under controlled condition. - Nahrawi, Hafsah; Mohd Hanif, Ahmad Husni; Othman, Radziah; Bah, Alagie (Malaysian Society of Soil Science, 2011)
A study examining the decomposition rates of leaf and fine root residues of oil palm (Elaeis guineensis), sago (Metroxylon sagu) and pineapple (Ananas comosus) crops in peatland soils was conducted under controlled conditions. The fourteen- month study showed that sago leaf residue was the most resistant to decomposition with only 30 % mass loss, while pineapple leaf residue was found to be the easiest to decompose, accounting for 90 % of the mass loss. In contrast, the highest (70 %) mass loss of fine roots was observed in sago, while the lowest (50 %) was in pineapple. Nutrient concentration in plant tissues correlated significantly with mass losses of leaf and fine root residues. The high C:N in plant tissues, resulted in slow decomposition of sago leaves and pineapple fine roots. Decomposition of the different plants were in the order: pineapple > oil palm > sago drained = sago undrained for leaf residues, and, sago drained = sago undrained > oil palm > pineapple for fine root residues.